2010
DOI: 10.1542/peds.2009-3362
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus 36 and Obesity in Children and Adolescents

Abstract: These data support an association of obesity and higher body weight with the presence of neutralizing antibodies to AD36 in children. If a cause-and-effect relationship is established, it would have considerable implications for the prevention and treatment of childhood obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
67
3
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(77 citation statements)
references
References 24 publications
5
67
3
2
Order By: Relevance
“…A cross-sectional study of 8-18-year olds in the USA also showed a clear association between Ad-36 seropositivity and obesity and body weight. 9 Although these results provide compelling support for the infectobesity concept, other studies do not support this concept. A study of Dutch and Belgian people found that Ad-36 infection was unlikely to be associated with obesity.…”
Section: Introductionmentioning
confidence: 80%
“…A cross-sectional study of 8-18-year olds in the USA also showed a clear association between Ad-36 seropositivity and obesity and body weight. 9 Although these results provide compelling support for the infectobesity concept, other studies do not support this concept. A study of Dutch and Belgian people found that Ad-36 infection was unlikely to be associated with obesity.…”
Section: Introductionmentioning
confidence: 80%
“…The worldwide nearly simultaneous manifestations of obesity can be explained by changes in food intake and exercise, but a contribution of infectious factors is plausible [35]. The association of Ad36 seropositivity with obesity is confirmed in adults [36] and in children [37][38][39]. Moreover, Ad36 seropositive status (Ad36?)…”
Section: Introductionmentioning
confidence: 99%
“…6,7 In addition, other studies using the Italian and the US children and adolescents demonstrated the association between the Ad-36 antibody and obesity. 8,9 Currently, little is known about the cellular and molecular mechanisms underlying Ad-36-induced obesity. Recently, Ad-36 E4 orf-1 was identified as a novel inducer of the rodent and human adipocyte differentiation process.…”
Section: Introductionmentioning
confidence: 99%